APICAL PERIODONTITIS IN MAXILLARY MOLARS WITH MISSED SECOND MESIO-BUCCAL ROOT CANAL: A CBCT STUDY - Cristina Coralia Nistor; Ioana Suciu; Ecaterina Ionescu; Anca Dragomirescu; Elena Coculescu; Andreea Băluță (Romanian Society of Oral Rehabilitation, 2024)
The aim of this study was to identify the prevalence of missed second mesio-buccal (MB2) root canal in root canal treated (RCT) maxillary first (MFM) and second molars (MSM) by means of cone-beam computed tomography (CBCT) and the association between missed MB2 and apical periodontitis (AP). Material and method. We analyzed 539 CBCT scanned maxillary molars (MM), from patients who visited two private offices over a period of five years. Results. The prevalence of RCT was 40.25%. The prevalence of AP among MM with RCT was 44.23%. The overall prevalence of missed MB2 canals was 52.53%. The overall prevalence of AP among MM with missed MB2 canals was 53.5%. 63.54% for MM with RCT and AP had missed MB2. Conclusions. There was a high prevalence of AP among endodontically treated maxillary molars. Also, there was a high prevalence of missed MB2 canal for these group of teeth and, consequently for the AP associated with a missed root canal.